Upaya Peningkatan Produktivitas Dengan Metode Objective Matrix (OMAX) - Raymond Christian Silaban (Jurnal Simetri Rekayasa, 2021)
Abstract The ability to compete in the indsutrial sector in Indonesia is going rapidly. Companies or UMKM to required to further improve quality and service to increase attractiveness to consumers. UD.Subur Jaya is an UMKM engaged in processingwood into frames and other appliances that process wood into cabinets, doors, windows, chairs and tables. Input control that has not been maximized due to erratic demand from consumers causes prodcutivity to fluctuate every month which causes problems on the production floor at UD.Subur Jaya. Therefore, an approach was taken using OMAX (Objective Matrix ). By calculating all the related inputs on the production floor, it is produced that in the month.